2013
DOI: 10.1105/tpc.113.115352
|View full text |Cite
|
Sign up to set email alerts
|

Expression Quantitative Trait Locus Mapping across Water Availability Environments Reveals Contrasting Associations with Genomic Features in Arabidopsis      

Abstract: The regulation of gene expression is crucial for an organism's development and response to stress, and an understanding of the evolution of gene expression is of fundamental importance to basic and applied biology. To improve this understanding, we conducted expression quantitative trait locus (eQTL) mapping in the Tsu-1 (Tsushima, Japan) × Kas-1 (Kashmir, India) recombinant inbred line population of Arabidopsis thaliana across soil drying treatments. We then used genome resequencing data to evaluate whether g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
92
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 72 publications
(101 citation statements)
references
References 96 publications
(155 reference statements)
8
92
1
Order By: Relevance
“…Our analysis of the parental genomes (sequences were published in Lowry et al, 2013) revealed that the chloroplast genomes of TSU and KAS were identical and only 16 SNPs existed in the mitochondrial genome. These results differed from published TSU-1 (SRX246442) and KAS-1 (SRX246466) sequences (http://www.ncbi.…”
Section: Documentation Of Genetic Network Through Qtl Mappingmentioning
confidence: 99%
See 4 more Smart Citations
“…Our analysis of the parental genomes (sequences were published in Lowry et al, 2013) revealed that the chloroplast genomes of TSU and KAS were identical and only 16 SNPs existed in the mitochondrial genome. These results differed from published TSU-1 (SRX246442) and KAS-1 (SRX246466) sequences (http://www.ncbi.…”
Section: Documentation Of Genetic Network Through Qtl Mappingmentioning
confidence: 99%
“…Only AT2G03140 had any sequence polymorphism between the TSU and KAS parental accessions (Supplemental Table 6). While gene function can easily be affected by polymorphism outside of the coding region, genes that are conserved between the widely divergent genomes of TSU and KAS may be less likely to contribute to quantitative genetic divergence than those with sequence, and especially protein, divergence (Lowry et al, 2013).…”
Section: Candidate Genes For Drought Adaptationmentioning
confidence: 99%
See 3 more Smart Citations